2017
DOI: 10.4103/jehp.jehp_134_16
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of hospitals' performance indicators before and after the Iran's hospital care transformations plan

Abstract: INTRODUCTION:Hospital care transformation plan (HCTP) was implemented, in 2014, with the aim of ensuring all Iranians have fair access to hospital care, mainly in the public sector. It was assumed that HCTP would lead to increased quality and effectiveness of health care in public hospitals. To explore whether HCTP has achieved its aim, this study has investigated the impact of this plan on performance indicators (PIs) of the public hospitals.MATERIALS AND METHODS:This cross-sectional descriptive study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Similar studies conducted in the hospitals affiliated to Bushehr University of Medical Sciences (Iran) also came to the conclusion that the plan has enhanced the bed occupancy rate and the average length of stay and the bed turnover ratio has also been steadily increasing (27). Also, the results of the study by Sajadi et al (2017) showed that BOR, ALOS, and BTR indicators have been increasing since the implementation of the HSRP (28). The number of patients admitted in the clinical and para clinical sections was also one of the other indicators concerned in this study, which showed an incremental increase following the implementation of the HSRP.…”
Section: Discussionmentioning
confidence: 54%
“…Similar studies conducted in the hospitals affiliated to Bushehr University of Medical Sciences (Iran) also came to the conclusion that the plan has enhanced the bed occupancy rate and the average length of stay and the bed turnover ratio has also been steadily increasing (27). Also, the results of the study by Sajadi et al (2017) showed that BOR, ALOS, and BTR indicators have been increasing since the implementation of the HSRP (28). The number of patients admitted in the clinical and para clinical sections was also one of the other indicators concerned in this study, which showed an incremental increase following the implementation of the HSRP.…”
Section: Discussionmentioning
confidence: 54%
“…However, the mean stay is lower than in this study, ranging from 4.00 to 5.67 days (3) . The reduction of the indicator was also verified in other institutions (23,25) , showing to be a problem-solving service and reducing risks due to prolonged hospitalizations and anticipating the individuals' return to society.…”
Section: Discussionmentioning
confidence: 70%
“…Regarding the Emergency Service, the output step is due to actions which aim to organize and direct the care process, which may encompass discharge, transference to another institution, or hospital admission (2) . In this sense, there is a tendency to organize and minimize time spent in services, aiming at the fastest possible solution, both in relation to hospital discharge and accommodation of clients in nursing beds, aiming at improving quality of care and the general result (18,(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…These days, various tools and methods are used to evaluate the performance of organizations, and if done correctly and continuously, it will improve the executive apparatus and performance and the efficiency and effectiveness of public and private sectors (9). One of the salient features of performance appraisal is that it has a quantitative aspect that converts the results and consequences of the appraisal into measurable values (10) and is a process that measures, evaluates, and judges' performance during specific periods (11). This study also showed the importance of establishing national emergency indicators in the hospital emergency department to improve services and patient satisfaction.…”
Section: Discussionmentioning
confidence: 83%